Common medicinal plants species found at burned and unburned areas of Klias peat swamp forest, Beaufort, Sabah Malaysia - Andy Russel Mojiol; Audrey Adella; Julius Kodoh; Walter Lintangah; Razak Wahab (Canadian Center of Science and Education, 2010)
The aims of this study is to survey the abundance and diversity of medicinal plants found in burned and unburned areas of Klias peat swamp forest, Beaufort. There are 16 plots established with the size of 25m x 25m for each plot with total area of 1 ha. All the plots were established using random sampling method and Simpson’s Index and Important Value (IV) were used to determine the diversity and abundance of the species. The result of the study shows that 11 species have been found in burned area while 10 species at unburned area. The most common medicinal plant species are identified as Stenochlaena palustris, Melastoma malabathricum, Lygodium flexuosum, and Clidemia hirta. The most abundant medicinal plant species found in burned area was Stenochlaena palustris with 185 percent (%). While in unburned area, the most abundant medicinal plants were Hedychium longicornutum and Lygodium flexuosum with 55 percent each. Simpson’s Index is higher with 0.55 in burned area compared in unburned area with only 0.14. Where when the value of Index increases, the diversity will decrease and this proved that diversity of medicinal plants in unburned area was slightly higher than the burned area. This situation might be caused by the previous land clearing due to burning and small scales landuses activities at the edges of Klias peat swamp forest. More research is needed in order to gain more precise data.